A novel ATP1A2 variant associated with severe stepwise regression, hemiplegia, epilepsy and movement disorders in two unrelated patients. (March 2021) - Calame, Daniel G.; Houck, Kimberly; Lotze, Timothy; Emrick, Lisa; Parnes, Mered
Abstract: Pathogenic variants in ATP1A2, a gene encoding the α subunit of the Na, K-ATPase, cause familial hemiplegic migraine type 2 (FHM2). In contrast, pathogenic variants in ATP1A3, an ATP1A2 paralog, cause alternating hemiplegia of childhood (AHC), a severe neurodevelopmental disorder with infantile onset hemiplegic attacks, seizures, dystonia, chorea and developmental delay. Despite high sequence homology with ATP1A3, ATP1A2 variants rarely associate with severe phenotypes resembling those linked to ATP1A3 . Here we describe two unrelated patients with infantile onset hemiplegic attacks, refractory epilepsy, movement disorders, abnormal eye movements and truncal ataxia with a shared de novo variant in ATP1A2, c.2438T > A (p.Met813Lys). The variant is not found in population databases, is predicted to be damaging by in silico analysis, and affects a highly conserved residue. Both patients experienced severe attacks with unilateral cerebral edema followed by sustained, stepwise regression. This report highlights the need to sequence ATP1A2 in the workup of patients with features of AHC that do not fulfill AHC diagnostic criteria. Highlights: ATP1A2 c.2438T > A (p.Met813Lys) is associated with infantile onset hemiplegic attacks, epilepsy, and movement disorders. Rare severe attacks with sustained, stepwise regression were seen in two patients with ATP1A2 c.2438T>A (p.Met813Lys). Clinicians should consider sequencing ATP1A2 in patients with infantile onset hemiplegic attacks, refractory epilepsy, and movement disorders that do not fulfill criteria for AHC.